Feasibility of Doppler Ultrasound for Cortical Cerebral Blood Flow Velocity Monitoring During Major Non-cardiac Surgery of Newborns - Costerus, Sophie A.; Kortenbout, Anna J.; Vos, Hendrik J.; Govaert, Paul; Tibboel, Dick; Wijnen, René M. H.; de Jong, Nico; Bosch, Johan G.; de Graaff, Jurgen C. (Frontiers in Pediatrics, 2021)
Background and aim: Newborns needing major surgical intervention are at risk of brain injury and impaired neurodevelopment later in life. Disturbance of cerebral perfusion might be an underlying factor. This study investigates the feasibility of serial transfontanellar ultrasound measurements of the pial arteries during neonatal surgery, and whether perioperative changes in cerebral perfusion can be observed and related to changes in the perioperative management. Methods: In this prospective, observational feasibility study, neonates with congenital diaphragmatic hernia and oesophageal atresia scheduled for surgical treatment within the first 28 days of life were eligible for inclusion. We performed transfontanellar directional power Doppler and pulsed wave Doppler ultrasound during major high-risk non-cardiac neonatal surgery. Pial arteries were of interest for the measurements. Extracted Doppler ultrasound parameters were: peak systolic velocity, end diastolic velocity, the resistivity index and pulsatility index. Results: In 10 out of 14 patients it was possible to perform perioperative measurements; the others failed for logistic and technical reasons. In 6 out of 10 patients, it was feasible to perform serial intraoperative transfontanellar ultrasound measurements with directional power Doppler and pulsed wave Doppler of the same pial artery during neonatal surgery. Median peak systolic velocity was ranging between 5.7 and 7.0 cm s-1 and end diastolic velocity between 1.9 and 3.2 cm s-1. In patients with a vasoctive-inotropic score below 12 the trend of peak systolic velocity and end diastolic velocity corresponded with the mean arterial blood pressure trend. Conclusion: Perioperative transfontanellar ultrasound Doppler measurements of the pial arteries are feasible and provide new longitudinal data about perioperative cortical cerebral blood flow velocity.